Additive manufacturing : materials, processes, quantifications and applications - Zhang, Jing; Jung, Yeon-Gil (Butterworth-Heinemann, 2018)
Additive Manufacturing: Materials, Processes, Quantifications and Applications is designed to explain the engineering aspects and physical principles of available AM technologies and their most relevant applications. It begins with a review of the recent developments in this technology and then progresses to a discussion of the criteria needed to successfully select an AM technology for the embodiment of a particular design, discussing material compatibility, interfaces issues and strength requirements. The book concludes with a review of the applications in various industries, including bio, energy, aerospace and electronics. This book will be a must read for those interested in a practical, comprehensive introduction to additive manufacturing, an area with tremendous potential for producing high-value, complex, individually customized parts. As 3D printing technology advances, both in hardware and software, together with reduced materials cost and complexity of creating 3D printed items, these applications are quickly expanding into the mass market.